2016
DOI: 10.1038/srep32415
|View full text |Cite
|
Sign up to set email alerts
|

Novel Foxp3− IL-10− Regulatory T-cells Induced by B-Cells Alleviate Intestinal Inflammation in Vivo

Abstract: Recent studies have revealed various Foxp3− regulatory T (Treg) cell subsets effectively protect mice from colitis. In the present study, we demonstrated that B cells induced a particular subset of regulatory T (Treg-of-B) cells, expressing programmed cell death 1 (PD-1), inducible costimulator (ICOS), lymphocyte-activation gene 3 (LAG3), glucocorticoid-induced tumor necrosis factor receptor (GITR), and OX-40, did not express Foxp3. Treg-of-B cells produced abundant levels of IL-10 and low levels of IL-4 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Treg-of-B cells have been demonstrated that protected mice from allergic asthma, arthritis, and inflammatory bowel disease2830313233. Peptide-induced antigen-specific Treg-of-B cells and monoclonal antibodies induced non-antigen-specific Treg-of-B cells possessed suppressive function.…”
mentioning
confidence: 99%
“…Treg-of-B cells have been demonstrated that protected mice from allergic asthma, arthritis, and inflammatory bowel disease2830313233. Peptide-induced antigen-specific Treg-of-B cells and monoclonal antibodies induced non-antigen-specific Treg-of-B cells possessed suppressive function.…”
mentioning
confidence: 99%
“…Moreover, Treg-of-B cells exerted IL-10-independent suppressive abilities and differed from Tr1 cells that mainly rely on IL-10-mediated inhibition. 6,7 These findings indicated that Treg-of-B cells have a regulatory T-related phenotype and new characteristics from the well-established Foxp3 + regulatory T cells and IL-10-dominant Tr1 cells.…”
mentioning
confidence: 88%
“…Indeed, it was shown that a mature immunologic synapse formed between naïve B cells and naïve T cells plays a key role in their suppressive activities. As for specific markers, Treg‐of‐B cells are characterized by high levels of Treg‐related molecules, such as CD44, GITR, ICOS, LAG3, and OX40, low levels of PD‐1 plus CTLA‐4 and no expression of Foxp3, Helios, and neuropilin‐1 . Also, Treg‐of‐B cells can produce large amounts of IL‐10, IL‐4, and TGF‐β compared to naïve T cells.…”
Section: Treg‐of‐b Cellsmentioning
confidence: 99%
“…While dendritic cell stimulation generates classical effector T cells, naïve B‐cell‐activated T cells show regulatory capacity in vitro and in vivo. Therapeutic effects of Treg‐of‐B cells have been described in several murine disease models, including intestinal inflammation, allergic asthma, and rheumatoid arthritis . The results of these trials suggest that Treg‐of‐B cells are beneficial for the treatment of a wide variety of diseases, although the clinical potential of Treg‐of‐B cells is just beginning to be realized.…”
Section: Treg‐of‐b Cellsmentioning
confidence: 99%
See 1 more Smart Citation